Development and physicochemical characterization of solid lipid nanoparticles containing tinidazole - Ho, Hoang Nhan; Le, Thi Thanh Ngoc; Le, Hoang Hao; Tran, Thi Kieu Ny; Dao, Anh Tuan (Tạp chí Y Dược Huế, 2023)
Background: Periodontitis is a chronic inflammation of the periodontal tissues. To increase the effectiveness of treatment, antibiotics selected should have a spectrum of action on bacteria causing periodontitis, while also meeting the requirements of cell penetration and prolonging of the retention time at the target site. Therefore, this study aimed at developing solid lipid nanoparticles (SLNs) containing tinidazole (TNZ-SLNs) oriented to be incorporated into the gel to increase the penetration ability and prolong drug retention time in periodontal tissues. Objectives: Therefore, this study aimed to develop and characterize solid lipid nanoparticles (SLNs) containing tinidazole (TNZ-SLNs) oriented to be incorporated into the gel to increase the penetration ability and prolong drug retention time in periodontal tissues. Methods: TNZ-SLNs were prepared by combining hot homogenization and solvent evaporation using different types of lipids and surfactants. Factors related to the formula and the preparation process were investigated, Design Expert 12.0, FormRules v2.0 and InForm v3.1 software were used to design experiments and optimize the formula. The prepared nanoparticles were characterized by particle size, polydispersity index (PDI), encapsulation efficiency (EE), etc. Results: The optimized formulation had a particle size of 197.60 ± 19.67 nm, a PDI of 0.247 ± 0.011, a zeta potential of -15.79 ± 0.75mV and an EE of 37.96 ± 0.91%. TNZ-SLNs showed prolonged in vitro drug release (for up to 24 hours), while TNZ material achieved about 100% drug release after 4 hours. Conclusion: TNZ-SLNs were successfully fabricated and physicochemically characterized.